Clinical characteristics and long-term prognosis of female patients with acute coronary syndrome - Rocamora-Horrach, Mar; Peiró, Óscar M.; Bardají, Alfredo; Flores-Benítez, Javier; Ivorra-Cámara, Miguel; Carrasquer, Anna; Ferreiro, José Luis (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular disease has traditionally been studied predominantly in men, but understanding its manifestations in women is crucial for effective management. This study aims to evaluate the long-term prognosis of female patients with acute coronary syndrome (ACS) within a tertiary hospital setting in Spain. Methods Retrospective observational study based on a cohort of consecutive hospitalized patients with ACS from January 2009 to December 2014. Data on demographics, risk factors, treatment, and outcomes were collected, with a median follow-up of 9.2 years. Results Women with ACS, constituting 27.3% of 2,330 patients, were older and had a higher prevalence of cardiovascular risk factors such as obesity, hypertension, and diabetes mellitus compared to men. They presented with more non-ST-segment elevation myocardial infarction and underwent less coronary angiography. Female patients were also less likely to be treated with acetylsalicylic acid, a second antiplatelet drug, or statins. Despite initial higher mortality rates [hazard ratio (HR) 1.30; 95% confidence interval (CI) 1.13–1.49; p < 0.001], female patients exhibited a more favorable long-term prognosis after adjustments (adjusted HR 0.82; 95% CI 0.71–0.96; p = 0.014), even in the subgroup analysis excluding patients with unstable angina. Conclusions Women with ACS are more comorbid, but after adjustments, female sex appears to be a protective factor that confers a better long-term prognosis.